2019
DOI: 10.1556/606.2019.14.3.13
|View full text |Cite
|
Sign up to set email alerts
|

Water body effect on microclimate in summertime: A case study from Pécs

Abstract: The relationship between water body (fountains) scale and climate parameters like wind speed, air temperature, relative humidity, as well as thermal comfort index was modeled and analyzed via Envi-met code. Taking the water impact and factors analysis as a research object, the factors mainly discussed in this research are square area to water-body area ratio and the location of the water element. However, the computational fluid dynamics simulations were conducted on the following scenarios: 3% (original base … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Syafii et al, [11] observed on average, 1.6 °C cooler pedestrian environment around the pond area. The experiment of Albdour and Baranyai [13] found the air temperature 0.6-1.5 K lower near the water element than the surrounding built-up area. All these studies tried to evaluate the comfort condition considering merely the air temperature as a key element of urban environment.…”
Section: Indoor Thermal Comfortmentioning
confidence: 93%
See 1 more Smart Citation
“…Syafii et al, [11] observed on average, 1.6 °C cooler pedestrian environment around the pond area. The experiment of Albdour and Baranyai [13] found the air temperature 0.6-1.5 K lower near the water element than the surrounding built-up area. All these studies tried to evaluate the comfort condition considering merely the air temperature as a key element of urban environment.…”
Section: Indoor Thermal Comfortmentioning
confidence: 93%
“…Their results suggest that both centralized and scattered water bodies can improve the microclimate of the residential district. Mohammad S. Albdour and Balint Baranyai [13] conducted a study to measure the effect of water features on the microclimate in Pecs, Hungary. Their results showed that water elements played a role in reducing air temperature and mean radiant temperature, while a slight effect on Predicted Mean Vote (PMV).…”
Section: Introductionmentioning
confidence: 99%
“…Studies with alternative vegetation and water redesign scenarios on urban squares with mitigation measure solutions were assessed through different scenario simulations using specific software tools (ENVI-met, SOLWEIG) for squares in Thessaloniki, Greece [78]; in Padua, Italy [79,80]; in Sétif, Algeria [81]; in Porto, Portugal [82]; in Achen, Germany [83]; in Cesena, Italy [84]; in Munich, Germany [85]; in Pécs, Hungary [86]; in Athens, Greece [87]; in Zurich, Switzerland [88]; in Guelma, Algeria [89]; in Mendoza, Argentina [90]; in Rome, Italy [91]; in Milan, Italy [92]; in Ishikawa, Japan [18]; and in Dalian, China [93].…”
Section: Cluster: Thermal Comfort and Heat Mitigation Measures-compar...mentioning
confidence: 99%
“…Numerous recent studies claim that green infrastructures are the most effective practices to promote cooling through shading, airflow orientation, precipitation interception, and evapotranspiration [ 92 , 93 , 94 , 95 , 96 , 97 ]. The combination of green infrastructure with blue infrastructure (water bodies) can cool the overlying and adjacent air through evaporation and convection [ 98 , 99 , 100 , 101 ]. As has recently been proven in China, PM2.5 pollution concentration decreases as environmental greenness increases, a phenomenon that was observed across different land cover types and cities [ 102 ].…”
Section: Urban Practices To Mitigate Soil Sealing: Typologies Charact...mentioning
confidence: 99%